2004
DOI: 10.1074/jbc.m408877200
|View full text |Cite
|
Sign up to set email alerts
|

p21-activated Kinase Regulates Endothelial Permeability through Modulation of Contractility

Abstract: Endothelial cells lining the vasculature have close cellcell associations that maintain separation of the blood fluid compartment from surrounding tissues. Permeability is regulated by a variety of growth factors and cytokines and plays a role in numerous physiological and pathological processes. We examined a potential role for the p21-activated kinase (PAK) in the regulation of vascular permeability. In both bovine aortic and human umbilical vein endothelial cells, PAK is phosphorylated on Ser 141 during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
154
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(170 citation statements)
references
References 50 publications
(44 reference statements)
14
154
1
1
Order By: Relevance
“…Thrombin induced vascular permeability dynamics of a similar nature in BAOECs have been elucidated in previous studies. [34][35][36]44,45 Figure 2 the tracer molecule in the abluminal channel is divided by the corresponding luminal concentration and compared along with thrombin treatment time. This normalizes the effect of doing the tests at different luminal concentrations to an extent and provides insight on how the size of the tracer molecule affects permeability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thrombin induced vascular permeability dynamics of a similar nature in BAOECs have been elucidated in previous studies. [34][35][36]44,45 Figure 2 the tracer molecule in the abluminal channel is divided by the corresponding luminal concentration and compared along with thrombin treatment time. This normalizes the effect of doing the tests at different luminal concentrations to an extent and provides insight on how the size of the tracer molecule affects permeability.…”
Section: Resultsmentioning
confidence: 99%
“…Supplementary material Figure S4 shows confocal images of leftover FITC dye in the lower channel before and after 6 ll data sample elution, showing the amount of tracer dye leftover to be minimal between each time points. The dosage and treatment time for thrombin to induce an increase in permeability on BAOECs was determined from other studies [34][35][36][37] and by performing cell permeability assays on transwell inserts.…”
Section: Permeability Assay In Bbv Modelmentioning
confidence: 99%
“…Dominant-negative Pak inhibits endothelial cell migration, whereas expression of a ␤Pix-binding Pak fragment inhibits endothelial tube formation (26,27). Pak also plays a role in permeability in human umbilical vein endothelial cells (HUVEC) and bovine aortic endothelial cells (BAEC) (28). It is not known whether ␤Pix is required for Pak activity during angiogenesis nor whether Pak plays the same roles in angiogenesis in vivo.…”
mentioning
confidence: 99%
“…Our data provide direct in vivo evidence that Pak2a function within the endothelial cell is specifically required for the formation of a stable vasculature, at least in a subset of vessels. Recent in vitro data have shown that PAK is involved in increasing vascular permeability in response to VEGF or other physiological signals (14,16). We hypothesize that the function of PAKs in the formation of vessels (angiogenesis) is different from its role in regulating endothelial cell permeability in already formed vessels.…”
Section: Discussionmentioning
confidence: 83%
“…PAKs, of which there are six family members in mammals, are kinases that act downstream of Rho-family GTPases and regulate a number of diverse biological processes that include immune function, apoptosis, stem cell self-renewal, cell motility, and cytoskeletal rearrangements (12,13). Alterations in PAK function in vitro have been shown to affect endothelial contractility, retraction, and migration (14)(15)(16)(17). PAKs are activated by the growth factors basic fibroblast growth factor and VEGF and have been implicated in angiogenesis (15,18) and formation of focal adhesions (19,20); however, there is very limited information available about the functions of PAK proteins in vivo (21).…”
mentioning
confidence: 99%